Long‐term changes in Italian mountain forests detected by resurvey of historical vegetation data. (2nd October 2020) - Lelli, Chiara; Nascimbene, Juri; Alberti, Davide; Agostini, Nevio; Zoccola, Antonio; Piovesan, Gianluca; Chiarucci, Alessandro
Abstract: Aim: In the last decades most European mountain forests have been abandoned after centuries of human management, paving the way for a landscape planning oriented to the conservation and rewilding of forest ecosystems. By resurveying historical vegetation plots in a mountain area of the Italian Apennines (southern Europe), we focused on yet overlooked processes in this area, to allow for a more comprehensive picture of the ongoing dynamics at a broad forest landscape scale. Location: Mountain forests in the northern Apennines, Italy. Methods: We resampled 22 historical forest vegetation plots recorded between 1934 and 1961. In each original quasi‐permanent plot, three plots were sampled to improve the reliability of the comparison. We analyzed changes in forest cover, structure, alpha, beta, and gamma diversity, and ecological groups focusing on the understorey species community. Results: Forests are getting poorer in species in the understorey, with a higher tree layer and denser canopy cover. Alpha and gamma diversity significantly decreased from the original to the resurveyed plots. Several species of open habitats were associated with the original plots, while in the resurveyed plots several shade‐adapted species were detected. Forest cover in the surroundings of the sites remained stable for the higher sites along the Apennines mountain ridge, while major changes in the surroundings and in species composition were detected for the plots located at lower elevations and marginal sites. Conclusions: Our main findings are in line with the majority of resurvey studies performed in European forests, with a general mesification of local communities after management cessation. Despite the limited number of available historical plots, their location along a wide gradient of elevation and naturalness allowed considering also the importance of site location, forest continuity and marginality as drivers of changes that need to be taken into account when planning conservation actions for restoration of mature forests. Abstract : With the resurvey of historical vegetation plots, we aimed to quantitatively assess forest vegetation dynamics in a rewilding, yet overlooked, mountain area of southern Europe, providing compositional and structural information to allow for a more comprehensive picture of the ongoing changes at a broad forest landscape scale.